Agent-based model simulation for ground penetration radar based on Netlogo platform - Hamid Bezzout; Hanan El Faylali (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Ground penetrating radar is used to detect magnetic materials underground by transmitting an electromagnetic wave into the material and receive the reflected pulse. In this paper, we develop a new agent-based model to simulate and evaluate the behavior of the ground penetrating radar based on Maxwell’s equations. This model contains several agents that represent the electric field, the magnetic field, the transmitted wave, the simulated medium, and the object to be detected. The implementation of this model is performed in Netlogo plaform because of its simplicity of coding and robustness of simulation. In order to validate our model, we have simulated the effect of the medium characterized by a dielectric constant and a conductance on the transmitted wave to evaluate the behavior of ground penetrating radar. The results obtained are compared with the literrature. Findings demonstrate that the transmitted pulse in the form of Gaussian pulse is reflected when it interacts with the object to detect. Thus, the ground penetrating radar can be efficiently simulated on Netlogo platform.